2017
DOI: 10.1186/s12864-016-3471-y
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing for global gene expression associated with muscle growth in a single male modern broiler line compared to a foundational Barred Plymouth Rock chicken line

Abstract: BackgroundModern broiler chickens exhibit very rapid growth and high feed efficiency compared to unselected chicken breeds. The improved production efficiency in modern broiler chickens was achieved by the intensive genetic selection for meat production. This study was designed to investigate the genetic alterations accumulated in modern broiler breeder lines during selective breeding conducted over several decades.MethodsTo identify genes important in determining muscle growth and feed efficiency in broilers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 93 publications
3
59
0
Order By: Relevance
“…Furthermore, interest in this transcription factor goes beyond stress. For example, when a comparison of a single male modern broiler line compared to a foundational Barred Plymouth Rock chicken line was conducted, it showed that Nrf2 expression in breast muscle was much higher in the modern broiler compared to the foundational BPR line [299], and it was suggested Nrf2-mediated oxidative stress response pathways are involved in breast muscle growth in chickens [300]. In recent years, several compounds, including carnitine, have been shown to have inhibitory activities against multiple components of the NF-κB activation pathway.…”
Section: Other Nutrients and Probioticsmentioning
confidence: 99%
“…Furthermore, interest in this transcription factor goes beyond stress. For example, when a comparison of a single male modern broiler line compared to a foundational Barred Plymouth Rock chicken line was conducted, it showed that Nrf2 expression in breast muscle was much higher in the modern broiler compared to the foundational BPR line [299], and it was suggested Nrf2-mediated oxidative stress response pathways are involved in breast muscle growth in chickens [300]. In recent years, several compounds, including carnitine, have been shown to have inhibitory activities against multiple components of the NF-κB activation pathway.…”
Section: Other Nutrients and Probioticsmentioning
confidence: 99%
“…Oxidative stress and impaired glycolysis can both arise due to mitochondrial dysfunction. Multiple studies have confirmed the transcriptomic [9,18] and metabolomic signatures of oxidative stress in WB [10], and have also suggested mitochondrial dysfunction [43]. Furthermore, genes essential to glycolysis, angiogenesis, and apoptosis (up-regulated in WB) are transcriptionally regulated in hypoxic conditions [44,45], that are typical of tissue under oxidative stress.…”
Section: Discussionmentioning
confidence: 87%
“…33 Kong et al reported that upregulation of LMOD2 gene responsible for skeletal muscle growth in broiler chickens. 34 Phosphoglycerate dehydrogenase (PHGDH) is a key metabolic enzyme in de novo serine biosynthesis. 35 Brown et al suggested that increased expression of PHGDH genes enhanced the skeletal muscle growth in ractopamine treated pigs.…”
Section: Discussionmentioning
confidence: 99%